Analysis of Marketing Strategy in Increasing the Sales of MSME Products of Ikat Mulya Woven Fabric Bandar Lor Kediri - Hanifah, Alif; Kusumaningtyas, Dian (Universitas Nusantara PGRI Kediri, 2025)
Research Objectives: This study aims to identify and analyze marketing strategies in increasing sales in MSMEs of Ikat Mulya Woven Fabric Bandar Lor Kediri. Design/Method/Approach: Using descriptive qualitative research methods, data collected through interviews, observation and analysis of documents related to the research. The source of this data comes from the marketing strategy process, while the object of the research is the MSMEs of Ikat Mulya Woven Fabric Bandar Lor Kediri. Research Findings: The findings in this study reveal the effectiveness of the marketing strategy owned by MSMEs in increasing sales of Mulya Ikat Woven Fabric products. Theoretical/Originality contribution: The contribution of this research lies in the disclosure of a combination of digital and conventional marketing strategies for MSMEs in the creative industry sector. Practitioner/Policy Implications: The results of this study provide guidance for MSME actors to utilize a combination of digital marketing strategies such as Instagram Ads and conventional strategies such as word of mouth to increase sales. Research limitations: The study was limited to the analysis of a single MSME in a specific geographical location and used a qualitative approach that did not allow for extensive generalization of results.